Contemporary Music in Central Italy: an Overview of Recent Decades - Mastropietro, Alessandro (Interdisciplinary Studies in Musicology, 2018)
The present article tries to make thematic the geographical plan of the present volume, by examining the major focal points of Contemporary Music in Central Italy which act as centres disseminating compositional trends through a long-established interest in recent music, as well as didactical structures and important teachers. Clearly, Rome is a more influential centre than Florence (where the endemic tendency of Florentine culture towards a sense of order, the settlement there of Dallapiccola, and the rise of a pioneering activity in the field of electronic music since the ‘60s are noteworthy); this is due to the teaching - through different generations - of Petrassi, Guaccero, Donatoni, Corghi and now Fedele, as well as the presence of many musical institutions, and the availability of artists and writers involved in exchanges and collaborations with composers. For this reason, many composers who were educated or active in Rome developed an outstanding - often prophetic - predilection for mix-media or theatrical works. After Bussotti, Guaccero, Macchi and Bertoncini, Giorgio Battistelli is a pivotal figure representing this trend in the next generation of composers; nonetheless an aptitude for it can be perceived also in other composers from both generations (Clementi, Pennisi and Renosto; Sbordoni, Lombardi, Rendine, D’Amico and De Rossi Re), including among the younger ones Silvia Colasanti, Roberta Vacca and Francesco Antonioni. In parallel, electronic music has been cultivated by Evangelisti and Branchi, as a way of renewing musical thought and language from their foundations: researches in the musical application of digital processing have been remarkable in Rome, along with experimentation in real time sound-generation and -transfoimation (Nottoli, Lupone, Di Scipio). On the whole, the generation born in the 1950s seems to tend (in aesthetics as well as in poetics) towards a change of thinking about musical form, integrating paradigmatic (structural) categories, typical of serial music, with syntagmatic (fictional) ones. Such an integration is perceivable as early as in the works of Donatoni, which have widely influenced many younger Italian composers, whether they have studied under him or not. The compositional horizon in Central Italy will be examined, with a special focus on that generation, with regard to two issues: 1) Has this change been determined (or helped) by post modernism? Before post-modernism became widespread during the 1980s, some composers from Rome had already elaborated a language which included heterogeneous sound materials and playing with musical codes, even if they did not deny the necessity of historical progress of musical language. Furthermore, postmodernism doesn’t suffice to explain the music of many composers, for whom the stratification of musical language and the sphericity of internal relationship inside a work is a result of the theory of complexity. 2) What is the aesthetical and poetical tendency in the youngest generation of composers, since a radicalization between a fictional and a visionary approach seems to have been established in their music?